Peningkatan Keterampilan Digital Marketing Melalui Metode Rebranding Produk Bagi Kelompok UMKM Di Kabupaten Banjarnegera - Fitri Adi Setyorini; M. Aris Pujiyanto (Arsil Media, 2023)
This journal discusses efforts to improve digital marketing skills in the context of empowering Micro, Small, and Medium Enterprises (MSMEs) groups in Banjarnegera Regency through the application of product rebranding methods. The main objective of this research is to increase the digital presence and competitiveness of MSME products in the online market. The research method involves collaboration between researchers and a selected group of MSMEs. The product rebranding process is carried out with a focus on developing brand identity, online layout, and digital marketing strategies. Special training is provided to members of the MSME group to increase their understanding of the use of digital platforms, social media, and other online marketing techniques. The research results show that the application of the product rebranding method significantly improves the digital marketing skills of the MSME group. We saw an increase in the number of website visitors, engagement on social media, and an increase in overall sales. In addition, members of the MSME group also reported an increase in their confidence and understanding of digital marketing strategies.